2013
DOI: 10.5121/ijit.2014.2401
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Contourlet-Based Hyperspectral Image Fusion Methods

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…For reconstruction, inverse Contourlet transform has to be applied. The basic flow of Contourlet based fusion framework (Choi et al 2013) is shown in Fig. 2.…”
Section: Contourlet Based Fusion (Ct)mentioning
confidence: 99%
“…For reconstruction, inverse Contourlet transform has to be applied. The basic flow of Contourlet based fusion framework (Choi et al 2013) is shown in Fig. 2.…”
Section: Contourlet Based Fusion (Ct)mentioning
confidence: 99%
“…Furthermore, wideband detection can perform in dust-filled environments, where infrared and optical systems fail [17]- [19]. Hyperspectral sensors and infrared system provides good resolution through exterior layers of an object [20]- [23]. However, penetration through denser objects (e.g.…”
Section: Wideband Technologymentioning
confidence: 98%
“…These methods are theoretically clear, but their framework is complex for estimation and the occurrence of incomplete deconvolution may result in an inefficient model. Multiscale and multiresolution methods extract high-frequency parts from HGRI and inject them into HSRI by decomposing the source image in a specific domain [17] [18] [19] [20] [21]. However, this type of method is highly dependent on the spectral properties of sampling methods and fails to intensify the spatial resolution of all bands.…”
Section: State Of the Artmentioning
confidence: 99%
“…Formulas (17) and 18have a similar mathematical form. Therefore, the ultimate fusion model can be achieved by replacing the variables in Formula (18) and updating rules in Formula (19) with the corresponding counterparts in Formula (17).…”
Section: Fusion Implementationmentioning
confidence: 99%